Membangun Iklim Sekolah Ramah Anak: Program Pencegahan Perundungan di SDN 010029 Desa Perkebunan Sukaraja - Rahmadani, Elfira; Lidiana Permata Sari, Putri; Azhari, Rahmad; Pradana Tamba, Andre; Syahida Siregar, Hanadia; Roma Utami, Naila; Sonita, Elvina (STMIK Royal, 2026)
Abstract: Bullying in Indonesian elementary schools continues to pose a significant threat to students' safety and well-being. In order to improve anti-bullying literacy, increase social awareness, and promote a secure and welcoming school environment, the